Angiogenesis in Breast Cancer: A Review - Gamde, Matthias Solomon; Ogenyi, Ochanya Destiny (Asian Pacific Journal of Cancer Biology, 2024)
Breast cancer is the leading cause of cancer related deaths worldwide. The development of new blood vessel from preexisting vasculature is associated to the growth and metastasis of breast cancer. The present review aimed to highlight the mechanisms of angiogenesis and the progression of malignancy in breast cancer. Poor breast cancer prognosis correlate with increased micro-vascular density and factors that stimulate vascular growth. Inhibiting angiogenesis of this process reduce the oxygen and nutrient supply. Therefore, tumor angiogenesis is a strategic therapeutic target for preventing breast cancer. We suggest the use of angiogenesis inhibitors to be explored to interrupt the process of tumor development.